Contemporary Adulthood
X, 173 p. 2 illus.
Keywords: A new approach which problematizes the category of contemporary adulthood, this book includes chapters on demographic change; becoming thirty-something; graduates and work; mental health and happiness; new configurations of masculinity; the sexual lifecourse; political beliefs in adulthood; and adulthood and the housing market.